2016
DOI: 10.3109/09638288.2016.1168488
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of Algo used by non-occupational therapist members of homecare interdisciplinary teams

Abstract: Purpose: To determine if non-occupational therapists (non-OTs) with different job titles using Algo, a clinical algorithm for recommending bathroom modifications (e.g., bath seat) for community-dwelling elders in ''straightforward'' situations, will make clinically equivalent recommendations for standardized clients. Method: Eight non-OTs (three social workers, two physical rehabilitation therapists, two homecare aides and one auxiliary nurse) were trained on Algo and used it with six standardized clients. Bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Older adults receive 1 of 9 possible recommendations [ 6 ], with or without assistive technology, specific to their bathing situation (ie, standing without a seat in the bathtub, sitting on a bath stool in the shower stall, or stop and refer to an OT). The content of the Algo was developed through an integrated knowledge approach [ 6 , 7 ], and psychometric studies [ 8 - 12 ] revealed, for example, that it guided non-OTs toward a bath seat that meets the needs of community-dwelling older adults in the majority of cases (mean 84%, SD 9%) [ 9 ]. The appropriateness rate of seats recommended by non-OTs did not statistically differ from that of 2 OTs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults receive 1 of 9 possible recommendations [ 6 ], with or without assistive technology, specific to their bathing situation (ie, standing without a seat in the bathtub, sitting on a bath stool in the shower stall, or stop and refer to an OT). The content of the Algo was developed through an integrated knowledge approach [ 6 , 7 ], and psychometric studies [ 8 - 12 ] revealed, for example, that it guided non-OTs toward a bath seat that meets the needs of community-dwelling older adults in the majority of cases (mean 84%, SD 9%) [ 9 ]. The appropriateness rate of seats recommended by non-OTs did not statistically differ from that of 2 OTs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%